Cross‐compartment proteostasis regulation during redox imbalance induced ER stress. Issue 15 (17th June 2014) - Maity, Shuvadeep; Basak, Trayambak; Bhat, Ajay; Bhasin, Namrata; Ghosh, Asmita; Chakraborty, Kausik; Sengupta, Shantanu
<x xml:space="preserve">Abstract</x> Imbalance in protein homeostasis in specific subcellular organelles is alleviated through organelle‐specific stress response pathways. As a canonical example of stress activated pathway, accumulation of misfolded proteins in ER activates unfolded protein response (UPR) in almost all eukaryotic organisms. However, very little is known about the involvement of proteins of other organelles that help to maintain the cellular protein homeostasis during ER stress. In this study, using iTRAQ‐based LC–MS approach, we identified organelle enriched proteins that are differentially expressed in yeast (Saccharomyces cerevisiae) during ER stress in the absence of UPR sensor Ire1p. We have identified about 750 proteins from enriched organelle fraction in three independent iTRAQ experiments. Induction of ER stress resulted in the differential expression of 93 proteins in WT strains, 40 of which were found to be dependent on IRE1. Our study reveals a cross‐talk between ER‐ and mitochondrial proteostasis exemplified by an Ire1p‐dependent induction of Hsp60p, a mitochondrial chaperone. Thus, in this study, we show changes in protein levels in various organelles in response to ER stress. A large fraction of these changes were dependent on canonical UPR signalling through Ire1, highlighting the importance of interorganellar cross‐talk during stress.